Shades of Rage: Applying the Process Model of Emotion Regulation to Managing Anger After Brain Injury - Witten, Jade Abigail; Coetzer, Rudi; Turnbull, Oliver H. (Frontiers in Psychology, 2022)
Uncontrollable anger is common following an acquired brain injury (ABI), with impaired emotion regulation (ER) being one of the main contributors. Existing psychological interventions appear moderately effective, though studies typically include limitations such as small sample sizes, issues of long-term efficacy, and standardization of content. While ER has been a popular research field, the study of ER for anger management after ABI is less well investigated, and contains few interventions based on the widely used Process Model of ER. This review surveys the efficacy of ER strategies in individuals with ABI, and proposes a novel research design for future interventions. Recommendations are made about: strategy number and type, shared decision-making, approaches to data analysis, and mode of delivery.